Soil acidification and nutrient imbalance under intensive black pepper plantations in the Central Highlands of Vietnam - NGUYEN VAN LONG; NGUYEN DO; NGUYEN THI VAN ANH; DINH THI NGOC HANH; VO CHI CUONG; NGUYEN QUANG NGOC; NGUYEN THI CAM VAN (Asian Journal of Agriculture, 2025)
Abstract. Long NV, Do N, Anh NTV, Hanh DTN, Cuong VC, Ngoc NQ, Van NTC. 2025. Soil acidification and nutrient imbalance under intensive black pepper plantations in the Central Highlands of Vietnam. Asian J Agric 9: 906-916. Black pepper, Vietnam's most valuable spice crop, is concentrated in the Central Highlands, where it plays a significant role in global supply, yet its long-term productivity is increasingly constrained by soil degradation. However, production is increasingly threatened by soil degradation and rising disease pressure. To evaluate substantial constraints, the soil fertility in 150 intensive black pepper plantations across Dak Lak, Dak Nong, and Gia Lai was assessed based on key physicochemical properties. Results revealed three critical constraints: (i) strong to very strong soil acidification (pH 3.55-6.40), (ii) low Cation Exchange Capacity (CEC 2.50-14.50 Cmolc kg-¹), and (iii) pronounced nutrient imbalances. Excessive phosphorus occurred in 82% of samples, while potassium deficiency affected up to 57.6% of plantations, with calcium and magnesium ratios varying substantially among provinces. Organic matter levels were generally adequate but unevenly distributed. Correlation and principal component analyses highlighted soil pH and organic matter as the primary regulators of nutrient availability. Notably, Dak Lak exhibited the strongest acidity and lowest CEC, Dak Nong showed more balanced fertility with higher CEC, and Gia Lai displayed higher nutrient levels but greater variability among farms. These constraints collectively reduce nutrient efficiency, weaken crop resilience, and intensify vulnerability to soilborne diseases. Practical interventions should therefore prioritize correcting acidity, enhancing buffering capacity, and managing nutrients in a balanced manner to sustain productivity and safeguard soil health. The findings provide an essential evidence base for soil restoration and sustainable intensification of black pepper cultivation in Vietnam's Central Highlands.